Influence of the bilayer thickness on the optical properties of Al2O3-Y2O3 dielectric nanolaminate films grown by thermal atomic layer deposition. (March 2017) - López, J.; Sotelo, A.; Castillón, F.F.; Machorro, R.; Nedev, N.; Farías, M.H.; Tiznado, H.
Graphical abstract: Highlights: Ultrathin nanolaminates based on Al2 O3 -Y2 O3 bilayers were successfully grown by ALD. The optical properties of Al2 O3 -Y2 O3 nanolaminates depend on the bilayer thickness. The refractive index and the optical bandgap of the nanolaminates can be modulated. The optical properties indicate that this material can be exploited for optical coatings. Combination of these materials is suitable for developing devices at nanoscale. Abstract: This work focuses on the study of the optical properties of nanolaminate films of Al2 O3 -Y2 O3 bilayers. Nanolaminates were grown by means of thermal atomic layer deposition (ALD). The multilayer thickness, refractive index and optical bandgap were studied via spectroscopic ellipsometry. Ellipsometric data revealed an increase of the refractive index from 1.9 to 2.2 at 190 nm wavelength when the bilayer thickness varies between 4 and 10 nm. These results demonstrate that the refractive index can be modulated by varying the nanolaminate thickness. Optical bandgap values, obtained by the Wemple and DiDomenico model, indicate that the bilayer thickness decrease leads to an increase of the optical bandgap (ΔEg  = 0.8 eV), as well as Eg modulation as a function of the bilayer thickness. The optical properties show that this material could be exploited for designing optical multilayered coatings suitable for nanoscale optoelectronic devices.